The Correlation between Macroeconomic Growth in India and the Performance of the Top 1,000 Companies over a 15-Year Period (2009-2023) - Alruwaily, Habibah (Journal of Global Economy, Business and Finance, 2024)
In this research, we have studied the evolution of the key macroeconomic parameters of the Indian economy, such as its GDP and GDP per capita, by taking the performance of the Indian corporate sector as a proxy. Within the Indian corporate sector, we have taken the top 1000 corporates listed on the National Stock Exchange (NSE) – a representative set that makes over 90% of the total market capitalization of the NSE companies and spanning over 12 key sectors of the economy – and have assessed their growth, profitability, capital investment, value - creation (as measured by ROIC exceeding the WACC) and market capitalisation trends over the last 15 years, clustered into three eras of five years each. These three eras correspond approximately, and respectively, to the second term of the UPA government during the post - financial crisis years (FY2009 - 2013), the first term of the NDA government (FY2014 - 2018), and the second term of the NDA/BJP government (FY2019 - 2023). The paper establishes how the sector mix of the economy has evolved over the last 15 years and shows clear variation across these sectors on their revenue growth, operational profitability (EBITDA), net profitability (PAT), and ROIC performance. In addition to deriving continued strong growth and profitability, we establish that a greater proportion of the corporates are now creating value, thus enabling them to raise their capital investment intensity, that sets the stage for further growth. We have also established a high - confidence and robust correlation between the absolute GDP (in turn, also the GDP growth) with the underlying revenue pool and EBITDA pool of the top 1000 corporates, with an R - squared value (R2) of 0.98, that provides a strong future predictor of the performance of Indian GDP and GDP growth based on the underlying performance of the top 1000 corporates in India.